Optimization of Boron Doped TiO2 as an Efficient Visible Light-Driven Photocatalyst for Organic Dye Degradation With High Reusability - Niu, Pingping; Wu, Guanghui; Chen, Pinghua; Zheng, Huitao; Cao, Qun; Jiang, Hualin (Frontiers in Chemistry, 2020)
No visible light activity is the bottle neck for wide application of TiO2, and Boron doping is one of the effective way to broaden the adsorption edge of TiO2. In this study, several Boron doped TiO2 materials were prepared via a facile co-precipitation and calcination process. The B doping amounts were optimized by the degradation of rhodamine B (Rh B) under visible light irradiation, which indicated that when the mass fraction of boron is 6% (denoted as 6B-TiO2), the boron doped TiO2 materials exhibited the highest activity. In order to investigate the enhanced mechanism, the difference between B-doped TiO2 and bare TiO2 including visible light harvesting abilities, separation efficiencies of photo-generated electron-hole pairs, photo-induced electrons generation abilities, photo-induced charges transferring speed were studied and compared in details. h+ and ·O2- were determined to be the two main responsible active species in the photocatalytic oxidation process. Besides the high degradation efficiency, 6B-TiO2 also exhibited high reusability in the photocatalysis, which could be reused at least 5 cycles with almost no active reduction. The results indicate that 6B-TiO2 has high photocatalytic degradation ability toward organic dye of rhodamine B under visible light irradiation, which is a highly potential photocatalyst to cope with organic pollution.